Perancangan User Experience Aplikasi Marketplace Wholesale "Supply" dengan Menggunakan Metode Human-Centered Design - Nisa' Luhung Mahbubah; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Technology has brought people's habits to be completely digital, especially in the economic field. Covid-19 is increasingly having an impact on economic behavior so that people are gradually changing their consumption patterns to online. Business actors must also change the marketing model to switch to online. In the product marketing process, of course, suppliers of goods are needed as suppliers to help get products that have value at affordable prices. In this study, designing a user experience design for a wholesale marketplace application to help business actors find suppliers so that they can get products easily through the application. The development method uses the Human Centered Design (HCD) method so that it can provide results from the analysis of the user context and user needs, the results of the solution design design and the results of the design evaluation. In the evaluation of the solution design using usability testing and filling out the User Experience Questionnaire (UEQ) to 10 respondents. The evaluation carried out resulted in a usability value with an effectiveness value of 84.5%, an efficiency value of 0.058 goals/second, and a user satisfaction value of 84.5 with a grade A+ predicate and a Best Imaginable rating. Benchmark results from user experience for wholesale application design have excellent scores for aspects of attractiveness, clarity, accuracy, and stimulation and good scores for aspects of efficiency and novelty.